Designed Manipulation of the Brassinosteroid Signal to Enhance Crop Yield - Lin, Wen-Hui (Frontiers in Plant Science, 2020)
Brassinosteroid (BR), a plant steroid hormone, plays crucial roles in modulating plant growth and development, which affect crop architecture and yield. However, BR cannot be applied directly in agricultural production because it regulates multiple processes in different tissues. In addition, the BR signal is not regulated at the transcriptional level. Effective manipulation of the BR signal and avoidance of side-effects are required to enhance yield in different crops. Application of BR by spraying at specific developmental stages can enhance crop yield, but this method is impractical for use on a large scale. The accurate molecular design of crops would be much more helpful to manipulate the BR signal in specific organs and/or at particular developmental stages to enhance crop yield. Here, we summarize the BR regulation of yield in different crops, especially horticultural crops, and the strategies used to regulate the BR signal to enhance crop yield. One popular strategy is to directly modulate the BR signal through modifying the functions of important components in the BR signal transduction pathway. Another strategy is to identify and modulate regulators downstream of, or in crosstalk with, the BR signal to manipulate its role in specific processes and increase crop yield. Efforts to accurately design a BR manipulation strategy will ultimately lead to effective control of the BR signal to avoid side effects and enhance crop yield.